Black bean protein concentrate ameliorates hepatic steatosis by decreasing lipogenesis and increasing fatty acid oxidation in rats fed a high fat-sucrose diet. Issue 12 (17th November 2020) - Hernandez-Velazquez, Irma; Sanchez-Tapia, Monica; Ordaz-Nava, Guillermo; Torres, Nimbe; Tovar, Armando R.; Galvez, Amanda
Abstract : The black bean is a legume widely consumed in Latin America, however its consumption has decreased significantly in recent decades. Abstract : The black bean is a legume widely consumed in Latin America, however its consumption has decreased significantly in recent decades. There is evidence that its consumption generates beneficial health effects due in part to the type of protein, resistant starches and polyphenols. Thus, their use in food formulation could impact health status. Therefore, the purpose of the present work was to evaluate the effects of the consumption of a bean protein concentrate (BPC) and a whole cooked bean flour (WCB) on body composition, glucose metabolism and energy expenditure in Wistar rats fed a control diet or high-fat diets with 5% sucrose in the drinking water. With this aim, rats were fed the experimental diets for 10 weeks. The results showed that consumption of either BPC or WCB reduced weight gain and body fat despite the consumption of a high-fat diet. This change was associated with a significant increase in energy expenditure and the capacity to adapt fuel oxidation to fuel availability. As a result, rats fed a bean-based diet had lower circulating glucose and insulin concentrations and normal glucose tolerance, which was associated with decreased expression of lipogenic genes in the liver. These results suggest that the type of protein and bioactive compounds particularly phenolic and flavonoid compounds present in BPC are suitable to improve the formulations used in dietary strategies for subjects with obesity or type 2 diabetes. The addition of legumes to the diet of subjects with insulin resistance, including black beans, could improve their metabolic status.